1988
DOI: 10.1088/0268-1242/3/5/011
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of porous silicon by Raman spectroscopy

Abstract: We have measured the room temperature Raman spectrum from porous films on silicon substrates. Data from films on degenerate substrates showed a Raman peak at the frequency expected for bulk silicon together with a peak shifted to lower frequencies. This was interpreted in terms of material having, in general, two different dimensions. Raman spectra from films on nondegenerate substrates show, in addition to the single crystalline peak, a broad wing extending to low frequencies. We have interpreted this as due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…31,32 These features can be supported by our Raman analyses, where we have determined nanocrystallite size of our PS samples. Different confinement models have been used to calculate particle size.…”
Section: 142829supporting
confidence: 62%
“…31,32 These features can be supported by our Raman analyses, where we have determined nanocrystallite size of our PS samples. Different confinement models have been used to calculate particle size.…”
Section: 142829supporting
confidence: 62%
“…Raman scattering was employed to gain more insight into the microstructure of the arrays. Numerous studies document Raman scattering from bulk Si, 38 amorphous Si, 39 and various nanostructured intermediates such as nanocrystals, [40][41][42] porous Si, 43 and nanowires. 44,45 For bulk Si in the backscattering geometry, the primary feature of the Raman signal is a sharp peak occurring near 520 cm À1 generated by the zonecenter LO phonon, with intrinsic full-width at half-maximum (FWHM) 38 $2.6 cm À1 corresponding to an energy relaxation timescale of $2.1 ps.…”
Section: Probing Microstructure Using Raman Spectroscopymentioning
confidence: 99%
“…Goodes et al 21 used Raman scattering to characterize the P-Si produced in the early years and interpreted the observed features associated with an amorphous component within P-Si. After the first observations of strong RT photoluminescence (PL) and electroluminescence (EL) from P-Si, Tsu et al 22 established a correlation between Raman and PL spectra and showed that the observed PL originates from extremely small microstructures.…”
Section: Raman Scattering From Porous Si Membranesmentioning
confidence: 99%